PROFIL SITOGENETIK KROMOSOM Y PADA LAKI-LAKI NORMAL - Wasilah, Siti (Jurusan Kedokteran FK Unsoed, 2010)
Normal prenatal developments of male and female genitalia are very complicated. Some crucial locion Y chromosome have a role in normal sexual development. Descriptive study about cytogenetics profile ofY chromosome presented in 30 normal male was done using G-banding and C-banding techniques todescribed the mean length and heterochromatin profile of y chromosome. Cytogenetics method using Gbandingshow 30 male with normal karyotype (46,XY) and there is no structure aberration of Y chromosome,the mean length of Y chromosome in normal male was 2,54 Î¼m (SD 0.31). Heterochromatin profile of Ychromosome analyzed by C-banding technique show that all normal male has C-band positive.